(untitled) (American Journal of Islam and Society, 2011)
Despite this being the age when information is readily available, the analysis, the dissemination, and the effect of pioneering Islamic knowledge in all fields is a relatively recent endeavor with only a handful of books that cover these areas from an academic point of view. The Muslim Contribution to the Renaissance is a comprehensive addition; it is a collection of numerous examples of Islamic innovation, and places these examples in their historical context in direct relation to the developing West—a time called the “Dark Ages”’ in Europe and the “Golden Age” in the Muslim world. This Golden Age was one of high calibre scholasticism and practical exploration in all fields, and it directly influenced the emergence in the West of what was to be called the “Renaissance.” ...